Beet curly top Iran virus Rep and V2 suppress post-transcriptional gene silencing via distinct modes of action - Ebrahimi, Saeideh; Eini, Omid; Baßler, Alexandra; Hanke, Arvid; Yildirim, Zeynep; Wassenegger, Michael; Krczal, Gabi; Uslu, Veli Vural (Viruses, 2023)
Beet curly top Iran virus (BCTIV) is a yield-limiting geminivirus belonging to the becurtovirus genus. The genome organization of BCTIV is unique such that the complementary strand of BCTIV resembles Mastrevirus, whereas the virion strand organization is similar to the Curtovirus genus. Geminiviruses are known to avoid the plant defense system by suppressing the RNA interference mechanisms both at the transcriptional gene silencing (TGS) and post-transcriptional gene silencing (PTGS) levels. Multiple geminivirus genes have been identified as viral suppressors of RNA silencing (VSR) but VSR activity remains mostly elusive in becurtoviruses. We found that BCTIV-V2 and -Rep could suppress specific Sense-PTGS mechanisms with distinct efficiencies depending on the nature of the silencing inducer and the target gene. Local silencing induced by GFP inverted repeat (IR) could not be suppressed by V2 but was partially reduced by Rep. Accordingly, we documented that Rep but not V2 could suppress systemic silencing induced by GFP-IR. In addition, we showed that the VSR activity of Rep was partly regulated by RNA-dependent RNA Polymerase 6 (RDR6), whereas the VSR activity of V2 was independent of RDR6. Domain mapping for Rep showed that an intact Rep protein was required for the suppression of PTGS. In summary, we showed that BCTIV-Rep and -V2 function as silencing suppressors with distinct modes of action.
Gesehen am 08.05.2024